A self-encryption authentication protocol for teleconference services. (22nd December 2006) - Jiang, Yixin; Lin, Chuang; Shi, Minghui; Shen, Xuemin Sherman
A novel authentication protocol for teleconference service is proposed. The main features of the proposed protocol include identity anonymity, one-time Pseudonym Identity (PID) renewal and location intracability. Identity anonymity is achieved by concealing the real identity of a mobile conferee in a prearranged PID. One-time PID Renewal mechanism, in which the mobile conferee's PID is frequently updated communicating with the network centre, is introduced to offer location untracability. It is shown that the security has been significantly enhanced, while the computation complexity is similar to the existing ones appeared in the literature.